Reduced abundance of Fusobacterium signifies cardiovascular benefits of sodium glucose cotransporter 2 inhibitor in type 2 diabetes: a single arm clinical trial - Shuhui Yang; Jiankun Deng; Xiaoxu Weng; Zhaojie Ma; Nie Lin; Yili Xiao; Rui Zuo; Yufei Hu; Canbin Zheng; Xiaoshan Zeng; Qimao Lin; Kaijian Hou; et al. (Frontiers in Pharmacology)
BackgroundThe sodium glucose cotransporter 2 inhibitor (SGLT2i) dapagliflozin has been demonstrated cardiovascular benefits in patients with type 2 diabetes mellitus (T2DM). However, the underlying mechanism remains poorly understood.MethodsWe conducted an 8-week, single-arm clinical trial, which enrolled 12 patients with inadequate glycemic control on metformin monotherapy. These patients were treated with SGLT2i dapagliflozin (10 mg/day). We assessed changes in clinical parameters pertinent to glucose metabolism and risk factors of cardiovascular disease (CVD), as well as alterations in the gut microbiota using macrogene sequencing.ResultsImprovements were observed in anthropometric parameters, glucose metabolism, blood lipid-related indices, inflammatory markers, and endothelial cell function-related parameters. Concurrently, SGLT2i led to changes in composition and functional pathways of the gut microbiota, manifested as increased abundance of probiotics and decreased abundance of harmful bacteria. Importantly, reduced abundance of Fusobacterium was correlated with improvements in various clinical indicators.ConclusionSGLT2i represents a superior initial therapeutic option for T2DM patients at risk of CVD. The cardiovascular benefits of SGLT2i may be attributed to shifts in the gut microbiota, particularly the reduced abundance of Fusobacterium.